Lost in transition? The returns to education acquired under communism 15 years after the fall of the Berlin Wall - Giorgio Brunello; Elena Crivellaro; Lorenzo Rocco (Institute for the Study of Labor (IZA), 2010)
Using data for 22 economies in Eastern and Western Europe, we find evidence that having studied under communism is relatively penalized in the economies of the late 2000s. This evidence, however, is limited to males and to primary and secondary education, and holds for eight CEE economies but not for the East Germans who have studied in the former German Democratic Republic. We also find that post-secondary education acquired under communism yields higher, not lower, payoffs than similar education in Western Europe.
Keywords: J24; 330; returns to education; Eastern Europe